Evaluation of the Anti-Ulcer Activity of Hydromethanolic Crude Extract and Solvent Fractions of the Root of Rumex nepalensis in Rats - Sisay Zewdu W; Jemere Aragaw T (Dove Medical Press, 2020)
Woretaw Sisay Zewdu,1 Tezera Jemere Aragaw2 1Department of Pharmacy, College of Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 2Department of Pharmacology, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tezera Jemere Aragaw Email tezeraadis1982@gmail.comBackground: Rumex nepalensis(RN) Spreng has been used to treat ulcer disease in Ethiopian folk medicine. This study aimed to determine the anti-ulcer activity of hydroalcoholic root crude extract and solvent fractions of R. nepalensis in rats.Methods: The effect of R. nepalensis crude hydromethanolic extract and solvent fractions at doses (100, 200, 400 mg/kg/day) and repeated dosing (200 mg/kg/day for 10 and 20 days) was examined on ulcers in rats in pyloric ligation-, cold restraint stress-, and acetic acid-induced ulcer models. Cimetidine (100 mg/kg/day) and/or Omeprazole (20 mg/kg/day) were used as standard drugs and served as a positive control. Data were analyzed by one-way ANOVA post hoc followed by a Tukey HSD test with SPSS software version 24.0, and P≤ 0.05 was considered as statistically significant.Results: In the pylorus ligation-induced ulcer model, pretreatment with the crude extract significantly reduced the degree of gastric secretions, pH, total acidity, and ulcerations in a dose-dependent manner. Gastroprotection offered by the R. nepalensis 400 mg/kg test extract was comparable to that of the standard. Among fractions, the ethyl acetate fraction at 400 mg/kg had the highest protection of ulcer but the chloroform fraction was ineffective. In the cold restraint stress-induced ulcer model, R. nepalensis at 200 and 400 mg/kg reduced the lesion index significantly (P< 0.01). With relevant chronic ulcer model treatment, a dose of R. nepalensis at 200 and 400 mg/kg healed ulcers significantly with a curative ratio of 53.22% and 54.59%, respectively.Conclusion: From this study, it is concluded that hydromethanolic crude extract and solvent fractions of R. nepalensis root showed promising anti-ulcer activity. This upholds its folkloric use. Thus, it is considered as a possible source to develop a new anti-ulcer agent.Keywords: pylorus ligation, stress ulcer, hydromethanolic extract, Rumex nepalensis